Teachers’ Job Performance and School Effectiveness in Public Senior Secondary Schools in Oyo State, Nigeria - Olabisi Aminat Owonwami; Oluwakemi Olabisi Akinnubi; Jamiu Olatunji Ottan; Abdullahi Ayinla Olokoba; Abubakar Adeleke Towobola (Universitas Islam Bunga Bangsa Cirebon, 2025)
The persistent underperformance of schools in Oyo State, Nigeria, has raised critical concerns about the effectiveness of teachers, whose roles are central to educational quality. This study investigated the impact of teachers’ job performance on school effectiveness in public senior secondary schools in the state. The objective was to examine how specific dimensions of job performance—lesson plan preparation, teaching methods, use of instructional materials, and record keeping—relate to school effectiveness. The study employed a descriptive survey design of a correlational type. From a population of 11,430 teachers across 563 schools, a stratified random sample of 387 teachers was drawn. Data were gathered using a validated